Screening of Particular Food-borne Pathogens in Raw Buffalos’ milk and some Popular Artisanal Egyptian Dairy Products - Alnakip, Mohamed E.A.; El-Essely , Engy; Bayoumi, Mohamed A.; Elsaid, Esmat E. (Journal of Advanced Veterinary Research, 2023)
Although their nutritive value and popularity, milk and dairy products frequently serve as a vehicle for the various pathogens of both human and animal origins. A wide variety of artisanal dairy products are produced in rural areas and villages of Egypt and due to lack of strict hygienic measures and lack of thermal treatment, these products usually harbor a variety of spoilage and possibly food-poisoning microorganisms. The current study aimed to investigate the contamination incidence of raw milk, Kariesh cheese and artisanal Yoghurt (Zabady) by staphylococci, E. coli and Bacillus cereus. Overall, 75 samples of raw milk (100.00%) were contaminated by staphylococci, 54 samples of karish cheese (72.00 %) contained E. coli, meanwhile, 45 samples of Zabady (60.00 %) yielded Bacillus cereus. Additionally, 29 out of 34 E. coli strains recovered from examined samples, were successfully serotyped with correspondence to 9 different serogroups, meanwhile 43 strains from different samples were untypable by available antisera. 80 out of all 162 E. coli isolates (49.38 %) carried haemolytic activity feature, which reflect a great threat towards consumers. Furthermore, the phenotypic AR of S. aureus and E. coli isolates was checked against eleven selected antibiotics. A remarkable variation in phenotypic AR was noticed among strains. Our results denote the high incidence of health hazards in raw milk and its products and the existence of AR S. aureus and E. coli strains isolated from milk and dairy products in rural areas, which could cause human illnesses that are difficult to be treated.